(untitled) (Anclajes, 2021)
In his poetic work, Aldo Oliva recovers historical discourses to intervene critically in them and rescue their disruptive potential buried by History. Within this frame, we analyze a few verses of his last poetic series, “Ese General Belgrano”, where the Argentinian hero is set against the hegemonic historical discourse that petrifies meanings and solidifies the course of the Revolution in a predetermined teleology. The verses show how the enjambment of voices (that of Belgrano and that of Oliva himself) discuss and subvert fossilized discourses and symbols: the thesis of the “preexistence of the Nation” defended by Mitre, and the Argentinian flag. Then, we situate this intervention in the particular (historical, political and poetic) context of production, in order to identify Oliva’s position. As a coda, we present the work of poets whose verses, in turn, reread Oliva’s poem on Belgrano.